Will You Buy My Peg? : The Credibility of a Fixed Exchange Rate Regime As a Determinant of Bilateral Trade - Jurzyk, Emilia (IMF Working Papers; Working Paper ;, 2004)
This paper examines the relationship between fixed exchange rate arrangements and trade using a gravity model of international trade together with bilateral trade data from 24 countries from the Caribbean and Latin America for the period 1960-2001. The analysis indicates that a credible fixed peg has a positive impact on the value of bilateral trade. Moreover, the positive impact on trade is more pronounced with a stricter definition of the fixed peg or a longer duration of the peg. This supports the argument that the credibility of an exchange rate peg is an important element to determine bilateral trade. There is, however, no evidence to suggest that a currency union provides additional benefits.